Endocardial Radiofrequency Ablation vs. Septal Myectomy in Patients With Hypertrophic Obstructive Cardiomyopathy: A Systematic Review and Meta-Analysis - Jiang, Tao; Huang, Bingyu; Huo, Shengqi; Mageta, Lulu Monica; Guo, Junyi; Lv, Jiagao; Lin, Li (Frontiers in Surgery, 2022)
Background Septal myectomy (SM) has been the gold standard therapy for most patients with hypertrophic obstructive cardiomyopathy (HOCM). Endocardial radiofrequency ablation of septal hypertrophy (ERASH) is a novel treatment for septal reduction. We aimed to assess the efficacy and safety between two treatment strategies. Methods We searched PubMed, Web of Science, Cochrane Library, and Embase databases to identify relevant studies published up to March 2021. Random-effect models were used to calculate standardized mean difference (SMD) and 95% confidence intervals (CIs) for resting left ventricular outflow tract gradient (LVOTG) and septal thickness. Results Twenty-five studies are included in this review, eighteen studies for SM and seven studies for ERASH. During follow-up, there were significant reductions of the mean resting LVOTG in adults (SM groups: SMD = −3.03, 95% CI [−3.62 to −2.44]; ERASH groups: SMD = −1.95, 95% CI [−2.45 to −1.45]) and children (SM groups: SMD = −2.67, 95% CI [−3.21 to −2.12]; ERASH groups: SMD= −2.37, 95% CI [−3.02 to −1.73]) after the septal reduction therapies. For adults, SM groups contributed to more obvious reduction than ERASH groups in interventricular septal thickness (SM groups: SMD = −1.82, 95% CI [−2.29 to −1.34]; ERASH groups: SMD = −0.43, 95% CI [−1.00 to 0.13]). The improvement of the New York Heart Association class was similar in the two groups (SM groups: 46.4%; ERASH groups: 46.7%). The periprocedural mortality in SM and ERASH were 1.1 and 1.8%, respectively. Conclusions This systematic review suggests that SM is superior to ERASH in the treatment of HOCM. But for the patients who are at risk for open cardiac surgeries or prefer a less invasive approach, ERASH might be an optional approach.